Dampak Pembangunan Adanya Industrialisasi Di Kabupaten Batang (Studi Kasus Desa Tulis) - Gilang Prasetyo; Wahyudiono; Demmy Adhi Mulya Darma (Fakultas Teknik dan Rekayasa, 2025)
Tulis District is an area designated as the center for the development of the Batang Regency Integrated Industrial Area as regulated in Presidential Regulation of the Republic of Indonesia number 109 of 2020. The aim of the Integrated Industrial Area development policy is to increase economic growth and community welfare. However, people are often not ready to accept and utilize a policy implemented by the government. This happens because of the lack of government involvement in planning the development of industrial areas. For this reason, research is needed to determine the impact of industrial development at PT. nest. The research method used in this research is a quantitative-qualitative descriptive approach. The data collection technique used to obtain primary data was through interviews and documentation with the community in Tulis Village. The results of this research show the impact of industrial development in Batang Regency. Keywords: Employee work safety